An Inquiry of Major Changes in the Methodology of Technical and Allocative Efficiencies in Economics: A Review of Literature - Rathnayake, R.M.A.K.; Amaratunge, S.P.P. (University of Sri Jayewardenepura, Nugegoda, 2011)
Efficiency measurements have been the concern of researchers with an aim to investigate the efficiency levels of almost all economic activities. Empirical estimation and identifying the determinants of efficiency are the major tasks in efficiency analysis. The main objective of this study is to investigate major changes taken place in the methodology of technical and allocative efficiency in Economics. The historical approach was used as the methodology of this study. There was no accepted statistical methodology to measure economic, technical and allocative efficiencies until the study of Farrell (1957); “The Measurement of Productive efficiency”. In Economics, economic efficiency has two components which are referred to as technical efficiency and allocative efficiency. Technical efficiency is associated with the ability to produce on the frontier isoquant, while allocative efficiency refers to the ability to produce at a given level of output using the cost-minimizing input ratios. Few alternative parametric methods are available in literature such as production, cost, profit, revenue and distance functions to analyze efficiency by estimating production technology. The nonparametric methodology involves mainly the use of linear programming techniques. According to available literature, it is clear that various approaches to efficiency analysis have been developed by two parallel traditions, the econometric method and the non-parametric data envelopment analysis. Both of these traditions incorporate its inherent merits and demerits. Findings of the study reveal that input distance function is the best methodology for measuring allocative efficiency if inputs quantities do not significantly vary across units of studies.
Keywords: Technical Efficiency; AllocativeEefficiency; Economic Efficiency